Development of Student Worksheets (LKPD) to Measure Student Creativity - Muhammad Arsyad; Helmi Helmi; Ummi Chalsum (Postgraduate, University of Mataram, 2023)
This research is a development research which aims to develop valid project based learning worksheets, practical project based learning worksheets, effective project based learning worksheets for measuring creativity. The subjects of this research trial were 32 students of class XI MIPA 2 SMAN 3 Polewali. This study uses the development of a 4-D model. The instruments used in this study were LKPD validation sheets, practitioner response questionnaires (educators/teachers), creativity test instruments and non-creativity test instruments (cognitive dimension creativity assessment sheets, affective dimension creativity questionnaires, psychomotor dimension creativity assessment sheets). LKPD eligibility criteria seen from the aspect of validity. The practicality criteria are seen from practitioners' assessment of LKPD, and the effectiveness criteria are seen from the level of creativity of students after being given project-based learning LKPD. Based on the results of the analysis, it was concluded that the developed project based learning LKPD, based on expert judgment using Aiken V index analysis, obtained a V value of 0.77 meaning that the LKPD was declared valid and feasible to use with minor revisions, then the project based learning based LKPD in terms of response physics teacher practitioners obtained an average score of 3.5 meaning that the LKPD is in the very good category and the effectiveness of project based learning LKPD is seen from the results of the analysis of student creativity, after being analyzed it is found that the average percentage of students' creativity scores on the cognitive dimension is 78.22%, the average percentage of creativity in the affective dimension is 79.25%, and the average percentage of creativity in the psychomotor dimension is 77.50% so that it can be said that the project based learning worksheets developed are effective for measuring student creativity because they have the average creativity score is above 75%.